Potential threats the rise of China's economic and military power in the Asia Pacific region - Tse, Kay; Ablaev, Ildar; Malkan, Omer (PT. Riset Press International, 2023)
Since long ago, international scholars have predicted that China will rise as one of the great powers in the international political economy. Based on China's potential to rise as the world’s number two power, this paper will discuss the forms of China's potential threats through economic and military means that can threaten the security of the Asia Pacific region. The main objective of this study is to examine the factors behind China's rise as a new power in the world economy and to identify the potential threat of China's military to the security of the Asia Pacific region. This study uses the concept of human security and security dilemma. The results of the study show that China has indeed succeeded in becoming a major power in the world economy after joining the WTO. However, the development of the international political economy today, shows that China has not fully challenged the existing international order through its military. China is seen to have worked hard to establish cooperation based on the spirit of the neighborhood and sustainable economic relations with countries in the Asia Pacific region and the United States.